Lactic acid bacteria population dynamics during minced beef storage under aerobic or modified atmosphere packaging conditions - Doulgeraki, Agapi I.; Paramithiotis, Spiros; Kagkli, Dafni-Maria; Nychas, George-John E. (Elsevier, 2010)
A total of 266 lactic acid bacteria (LAB) have been isolated from minced beef stored at 0, 5, 10 and 15 °C aerobically and under modified atmosphere packaging consisting of 40% CO2–30% O2–30% N2 in the presence MAP (+) and absence MAP (−) of oregano essential oil. Sequencing of their 16S rRNA gene along with presence of the katA gene demonstrated dominance of the LAB microbiota by Leuconostoc spp. during aerobic storage at 5, 10 and 15 °C, as well as during MAP (−) and MAP (+) storage at 10 and 15 °C; Lactobacillus sakei prevailed during aerobic storage at 0 °C, as well as at MAP (−) and MAP (+) storage at 0 and 5 °C. The sporadic presence of other species such as Leuconostoc mesenteroides, Weisella viridescens, Lactobacillus casei and Lactobacillus curvatus has also been determined. Pulsed-Field Gel Electrophoresis of high molecular weight genomic DNA revealed the dynamics of the isolated LAB strains. Prevalence of Leuconostoc spp. was attributed to one strain only. On the other hand, packaging conditions affected Lb. sakei strain spoilage dynamics.
Keywords: Lactic acid bacteria; Meat preservation; PFGE; Essential oils; Microbial ecology